2021
DOI: 10.1111/apt.16407
|View full text |Cite
|
Sign up to set email alerts
|

Umbrella review of 42 systematic reviews with meta‐analyses: the safety of proton pump inhibitors

Abstract: Summary Background Proton pump inhibitors (PPIs) are widely used to treat and prevent acid‐related disorders. Despite high efficacy, PPI safety has been increasingly scrutinised. However, no comprehensive review summarising investigations of various adverse events is available. Aims To perform an umbrella review to comprehensively assess associations between adverse events and PPI use. Methods In accordance with PRISMA, an umbrella review of systematic reviews with meta‐analyses was conducted. PubMed and EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 74 publications
(227 reference statements)
2
41
0
2
Order By: Relevance
“…The included articles were published between 2009 and 2021. The descriptive characteristics of T A B L E 1 Criteria for quality of evidence classification in meta-analysis of observational studies [10][11][12][13] Category Criteria…”
Section: Meta-analyses Of Cohort Studiesmentioning
confidence: 99%
“…The included articles were published between 2009 and 2021. The descriptive characteristics of T A B L E 1 Criteria for quality of evidence classification in meta-analysis of observational studies [10][11][12][13] Category Criteria…”
Section: Meta-analyses Of Cohort Studiesmentioning
confidence: 99%
“…There is no increase in PPI acceptance over time (no correlation shown in multivariate analysis) while misuse and adverse effects and drug interactions are increasingly described in the scientific literature [ 1 , 3 5 , 8 , 10 , 27 ]. Data from the literature underlined that lack of time and perceiving PPIs as “harmless” affect physicians' decision making [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…)-negative peptic ulcer disease, treatment and prophylaxis of NSAID-associated gastric ulcers, and management of gastric acid hypersecretory states [1]. Despite their efficacy, long-term use of PPIs has been linked to several adverse effects [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Biological plausibility for the presumed PPI - COVID-19 relationship is based on reduced antiviral resistance due to prolonged gastrointestinal hypochlorhydria and subsequently increased pulmonary colonization [5, 6, 8]. Theoretically, the (presumed) effects on gut microbiome and micronutrient deficiencies [7, 8] might contribute. Two questions about pre-morbid PPI use seem to naturally arise from this mechanistic rationale: one pertaining to the risk of infection and the other one to the risk of severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term PPI use has been suggested associated with the risk of worsening or incidence of variety of diseased conditions [5, 6]. Two recent comprehensive evaluations demonstrated that quality of evidence relating PPIs as potential causes to these adverse events was “low” or “very low” predominantly for the following reasons: mostly observational data, modest effects commonly burdened by residual confounding, bias by indication, protopathic bias and data inconsistency [2, 7].…”
Section: Introductionmentioning
confidence: 99%